The Yin and Yang of Immunity in Stem Cell Decision Guidance in Tissue Ecologies: An Infection Independent Perspective - Garg, Vaishali; Chandanala, Shashank; David-Luther, M.; Govind, M.; Prasad, Roshni Ravi; Kumar, Anujith; Prasanna, S. Jyothi (Frontiers in Cell and Developmental Biology, 2022)
The impact of immune system and inflammation on organ homeostasis and tissue stem cell niches in the absence of pathogen invasion has long remained a conundrum in the field of regenerative medicine. The paradoxical role of immune components in promoting tissue injury as well as resolving tissue damage has complicated therapeutic targeting of inflammation as a means to attain tissue homeostasis in degenerative disease contexts. This confound could be resolved by an integrated intricate assessment of cross-talk between inflammatory components and micro- and macro-environmental factors existing in tissues during health and disease. Prudent fate choice decisions of stem cells and their differentiated progeny are key to maintain tissue integrity and function. Stem cells have to exercise this fate choice in consultation with other tissue components. With this respect tissue immune components, danger/damage sensing molecules driving sterile inflammatory signaling cascades and barrier cells having immune-surveillance functions play pivotal roles in supervising stem cell decisions in their niches. Stem cells learn from their previous damage encounters, either endogenous or exogenous, or adapt to persistent micro-environmental changes to orchestrate their decisions. Thus understanding the communication networks between stem cells and immune system components is essential to comprehend stem cell decisions in endogenous tissue niches. Further the systemic interactions between tissue niches integrated through immune networks serve as patrolling systems to establish communication links and orchestrate micro-immune ecologies to better organismal response to injury and promote regeneration. Understanding these communication links is key to devise immune-centric regenerative therapies. Thus the present review is an integrated attempt to provide a unified purview of how inflammation and immune cells provide guidance to stem cells for tissue sculpting during development, organismal aging and tissue crisis based on the current knowledge in the field.